IMPROVING THE QUALITY OF EDUCATIONAL SERVICES THROUGH EFFECTIVE COLLABORATION IN MADRASAH - Syamsiyah, Munawaratus (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to analyze and understand the process of improving the quality of educational services through effective collaboration in madrasas. This research was conducted using a qualitative case study type approach. This research was conducted at the Madrasah Ibtidaiyah Nurul Yaqin Yayus Yunus Kertosono Gading Probolinggo institution. The data analysis technique in this research uses the Miles and Huberman data analysis model with stages of data reduction, data display, and drawing conclusions. Based on the results of research conducted, it shows that in its application; (1) The use of technology, especially web-based and mobile applications, has helped facilitate communication and collaboration between members of the education team at the madrasah. (2) Training and development of madrasa educators Madrasah Ibtidaiyah Nurul Yaqin Yayus Yunus Kertosono Gading Probolinggo increasingly recognizes the importance of continuous training and development for educators. (3) Partnerships with local communities specifically strengthen service quality by involving local communities in educational efforts. (4) Increasing parent-teacher communication in order to improve educational services in madrasas. So the synergy of teamwork in improving educational services underlines how important teamwork is in the context of the Madrasah Ibtidaiyah Madrasah Ibtidaiyah Nurul Yaqin Yayus Yunus Kertosono Gading Probolinggo